การขยายพันธุ์ขมิ้นชัน (Curcuma Longa L.) ด้วยตายอดจากเหง้าอ่อน - กรภัทร์ชัยกุล กรณ์ (Science Essence Journal, 2015)
การพัฒนาวิธีการชักนำให้เกิดยอดอย่างมีประสิทธิภาพในขมิ้นชัน (Curcuma longa L.) 2 ชนิด ที่เก็บตัวอย่างมาจากอำเภอบ้านตาขุนและอำเภอท่าชนะในสภาพปลอดเชื้อ โดยการตัดปลายยอดจากเหง้าอ่อนไปวางเลี้ยงบนอาหารสูตร MS (Murashige and Skoog, 1962) ที่เติม Malt extract 100 มก./ล. และ BAP ความเข้มข้นต่างๆ เป็นเวลา 45 วัน ผลการทดลองพบว่า BAP ความเข้มข้น 3.5 มก./ล. ทำให้เกิดหน่อเฉลี่ยสูงสุดทั้งสองชนิด (4.58 และ 4.21 หน่อ ตามลำดับ) เมื่อทดลองย้ายหน่อมาเพาะเลี้ยงบนอาหารใหม่สูตรเดิมหลายชั่วรุ่นพบว่าอัตราการเกิดหน่อมีแนวโน้มลดลงทั้งสองชนิด หน่อที่เกิดขึ้นสามารถเกิดรากได้เองในอาหารที่เติม BAP ที่เพาะเลี้ยงเป็นเวลานาน เมื่อเติมผงถ่าน 100 มก./ล. สามารถทำให้เกิดรากอย่างรวดเร็วและจำนวนมาก การอนุบาลต้นขมิ้นชันที่มีรากสมบูรณ์ด้วยวิธีการต่างๆ พบว่า ต้นขมิ้นชันที่ตัดใบละครึ่งนำลงปลูกในกระถางดินแล้วครอบด้วยถุงพลาสติกใสทำให้มีอัตรารอดตายสูงสุดทั้งสองชนิด (ร้อยละ 95 และ 98.5 ตามลำดับ) จากการสังเกตลักษณะทางสัณฐานของต้นขมิ้นชันที่เกิดขึ้นจากการเพาะเลี้ยงตายอดจากเหง้าอ่อนทั้งสองชนิดจำนวนมากไม่พบลักษณะผิดปกติที่แตกต่างจากต้นแม่ In order to develop an efficient regeneration protocol for turmeric (Curcuma longa L.) shoot-tip cultures which sample plants collected from Bantakhun and Thachana districts. The sterile shoot-tips were dissected from juvenile rhizome and initiated on MS medium supplemented with 100 mg/L malt extract and various concentrations of BAP for 45 days. The results showed that the MS medium containing 3.5 mg/L BAP fortified the maximum buds number production (4.58 and 4.21 shoots, respectively). Multiplication rates studied by subculturing every 45 days interval for ten times tended to decreased shoot buds numbers significantly. The shoot bud clusters were rooted spontaneously in the multiplied medium containing BAP, which applying in a long period. Adding 100 mg/L activated charcoal in the rooting medium ameliorated the number and quality of roots. Leaves clipping in half and transparent plastic bags covering were the best result to thriving acclimatization, and transplantation was taken successful under high humidity and low light intensity resulting in highest survival rate (95 and 98.5%, respectively). Morphological traits investigation of numerous turmeric plants derived from in vitro culture did not differ with maternal plants.